Monstrous Mothers: The Grotesque and Doubling in Contemporary American Literature's Maternal Figures - Henrique, Morgan Rizzo (My University, 2023)
This thesis examines contemporary American literature’s representation of mothers who fail to meet societal expectations for motherhood. These mothers are products of intersectional oppression, including oppression based on race, gender, sexuality, and immigration status. My aim is to highlight these misrepresented experiences as less “monstrous” and more real--as reflections of the realities of twentyfirst century motherhood and reminders that motherhood is transformational, laborious, and oftentimes the opposite of what our initial expectations may be. It offers an interpretation of Charlotte Perkins Gilman’s “The Yellow Wallpaper,” as representative of the specific constraints the patriarchy places on motherhood, rather than reducing the text to a purely anti-patriarchal reading. It follows with readings of Carmen Maria Machado’s “Mothers” from Her Body and Other Parties and Ocean Vuong’s novel, On Earth We’re Briefly Gorgeous, as testaments of intersectional oppression against mothers. Each of these mothers is working towards some form of self-healing while simultaneously adapting to an ideal of motherhood that is unattainable. Using Lacan’s Mirror Stage as a guiding force, along with taking Grendel’s mother and using her as an archetype for these “monstrous mothers,” this thesis hopes to illuminate the stories of mothers who are often rejected. The grotesque and doubling are genre-specific mechanisms that help give voice to the othered experiences of these mothers. The narrator in “The Yellow Wallpaper” sees herself doubled with the woman in the wallpaper; and both the narrator in “Mothers” and the character of Bad can be read as mirrored representations of motherhood. Little Dog in On Earth We’re Briefly Gorgeous sees a mirrored connection with his and his mother’s approach to coping with their traumas. While there is a plethora of canonical and contemporary texts that I could have examined for this thesis, I chose to highlight traditionally-overlooked voices and to emphasize the intersectionality of the oppression faced by these maternal figures. By rejecting the ideal of the passive mother, we can offer a message of hope to new mothers who are searching to redefine themselves postpartum. Oftentimes the traumas surrounding postpartum depression extend past the immediacy of the mother and child. Instead, systemic oppression and generational trauma are contributing factors that should not be ignored. This thesis uses the narrator in Charlotte Perkins Gilman’s “The Yellow Wallpaper,” the mother in Ocean Vuong’s On Earth We’re Briefly Gorgeous, and the narrator in Carmen Maria Machado’s “Mothers'' as vehicles for unpacking the victimization, ostracization, and vilification of mothers whose stories fail to meet Western ideals. Keywords: Carmen Maria Machado; doubling; grotesque; maternal archetype; Ocean Vuong; the Yellow Wallpaper
Keywords: English; Literature; Academic theses